The Effect of Auditory Stimulation Theraphy for Baby’s Pain Scale - Fatma Zulaikha; Enok Sureskiarti; Nunung Herlina; Syarifah Hindun; Murti Handayani (Indonesian Journal of Global Health Research, 2021)
Auditory stimulation is one of non-pharmacological pain management that can be done in premature babies by playing music or mother's voice with an acceptable to the baby (50-60 dB). This study aimed to analyze the effect of giving music therapy and mother’s voice theraphy in controlling the pain response of premature babies while undergoing an invasive procedure. The research design used in this study was a quasi-experimental research with pre and posttest one group design, purposive sampling used in this study, involving 43 premature babies in a Samarinda Hospital. Observation checklist was further used for data collection. Based on the paired t-test, it obtained a sig-value of 0.000 (p <0.05) with a difference of 5.535 (95% CI 4.682 - 6.388) for music theraphy and sig-value of 0.000 with a difference of 5.860 (95% CI 5.204 - 6,517) showing a sig value <0.05 for mother's voice during the invasive procedure. The analysis showed that there were significant differences before and after giving auditory stimulation of the mother's voice during an invasive procedure.